U.S. Economic Diplomacy: Analysis of Recommendations for American Exporters Operating in Uzbekistan - Khallakova Nigorabonu Erkin qizi; Ishmuradov Bahodir Sunnatovich (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract: The article analyses recommendations contained in official reports by the US State Department intended for American exporters planning to operate in Uzbekistan. The focus is on the annual Investment Climate Statements for the last five years, which provide a comprehensive assessment of the legal, regulatory and investment environment and are used by companies as a practical basis for risk analysis and export project preparation. Additionally, the Country Commercial Guide: Uzbekistan and bilateral Fact Sheets containing information on the business environment and institutional support mechanisms are examined. Based on these sources, the main areas of recommendations have been systematised, including market entry strategies, legal and financial requirements, risk assessment and compliance with export control regulations. It is shown that the official reports of the State Department serve a dual function: they provide reliable information about the specifics of the Uzbek market and serve as a tool for practical economic diplomacy by the United States.